To Assess The Impact Of Socioeconomic Factors On Deciduous Teeth Eruption Among Infants Born After Low-Risk Pregnancy And Infants Diagnosed With Intrauterine Growth Restriction (IUGR) - Kambli, Vinod; Purohit, Shweta; Mehta, Trisha; Gautam, Ashesh; Poddar, Nayanika; Mutha, Madhur Nitin (Journal of Neonatal Surgery, 2025)
Aim:To assess the impact of socioeconomic factors on deciduous teeth eruption among infants born after low-risk pregnancy and infants diagnosed with intrauterine growth restriction (IUGR). Material and Methods: This cross-sectional observational study included 110 infants aged 6–18 months, divided equally into two groups: infants born after low-risk pregnancies (control group) and those with IUGR. Demographic, perinatal, and socioeconomic data were collected through interviews and medical records. Clinical oral examinations were conducted to assess the presence and number of erupted deciduous teeth. Statistical analyses included t-tests, chi-square tests, and multivariate regression to identify associations between IUGR, socioeconomic variables, and tooth eruption. Results: Infants with IUGR had significantly lower birth weights (p < 0.001) and gestational ages (p = 0.003) than controls. Socioeconomic disadvantages, including lower parental education, income, and healthcare access, were more prevalent in the IUGR group. Delayed tooth eruption was significantly higher in IUGR infants (50.91%) compared to controls (20.00%, p = 0.001). Multivariate analysis revealed IUGR as an independent negative predictor of the number of erupted teeth (β = -1.25, p = 0.002), while maternal education, household income, and healthcare access were positively associated. Conclusion: IUGR significantly delays the eruption of primary teeth, a delay further exacerbated by socioeconomic disadvantage. These findings underscore the importance of early dental and developmental surveillance in at-risk populations and highlight the need for public health efforts to address socioeconomic disparities.